The Development of Reading Ability Words by using Game-based learning for Prathomsuksa 3 students - เชื้อบัณฑิต, พัชริยา; Yeekengaem, Sariyagan; Phitchayapirath, Piyaporn (Ubon Ratchathani Journal of Research and Evaluation, 2024)
The purpose of this research was to compare the development of reading Ability words before and after learning by using game-based learning for prathomsuksa 3 students and and to study the satisfaction of prathomsuksa 3 students with development for reading Ability words by using game-based learning for Prathomsuksa 3 students The research samples were 14 students in Grade 3 students from Nadeedonjan School in Yasothon Province. The selection of the sample was Cluster sampling the research instruments consisted of seven learning management plans, a test to measure reading Ability words, a test to measure reading Ability words, 4 options, 30 items; and a three-rating scale questionnaire used to evaluate the satisfaction of the students towards learning by using the reading activity packages for reading ability words with the statistics used to analyze data were mean, 10 items; standard deviation, and a Wilcoxon signed rank test. The research findings were as follows: The results of comparing the reading ability words of grade 3 students using game-based learning for prathomsuksa 3 students showed the that that the mean score before the intervention was 13.64 points, while after the intervention, the mean score was 24.43 points. The results also indicated that the mean score after the intervention was statistically higher than the mean score before the intervention at the .05 level of significance which met the hypothesis regulated. The results of satisfied level reading ability words by using game-based learning for Prathomsuksa 3 students with the average score of 2.84 and with the standard deviation score of 0.31 in the overall at a high level.